Cryobanking of aquatic species - Martinez-Paramo, Sonia (2017)
This review is focused on the applications of genome cryobanking of aquatic species including freshwater and marine fish, as well as invertebrates. It also reviews the latest advances in cryobanking of model species, widely used by the scientific community worldwide, because of their applications in several fields. The state of the art of cryopreservation of different cellular types (sperm, oocytes, embryos, somatic cells and primordial germ cells or early spermatogonia) is discussed focusing on the advantages and disadvantages of each procedure according to different applications. A special review on the need of standardization of protocols has also been carried out. In summary, this comprehensive review provides information on the practical details of applications of genome cryobanking in a range of aquatic species worldwide, including the cryobanks established in Europe, USA, Brazil, Australia and New Zealand, the species and type of cells that constitute these banks and the utilization of the samples preserved. Statement of relevance: This review compiles the last advances on germplasm cryobanking of freshwater and marine fish species and invertebrates, with high value for commercial aquaculture or conservation. It is reviewed the most promising cryopreservation protocols for different cell types, embryos and larvae that could be applied in programs for genetic improvement, broodstock management or conservation of stocks to guarantee culture production. (C) 2016 Elsevier B.V. All rights reserved.